Model Pemberdayaan UMKM Perikanan melalui Integrasi Inovasi Produk Dimsum Bandeng, Branding, dan Digital Marketing di Desa Gumeng, Gresik - Dia Puspitasari; Muhammad Idrus; Revalina Dwi Anggita; Ainur Rahmalita; Adrian Maulana (Yayasan Cendekia Gagayunan Indonesia, 2026)
Background: Milkfish (bandeng)-based micro, small, and medium enterprises (MSMEs) in coastal villages of Indonesia remain underdeveloped, as shown by the PKK Mawar Mekar women's group in Gumeng Village, Gresik, which still relies on raw or traditionally processed milkfish with low added value and limited branding and digital marketing capacity. Purpose: This study aims to formulate an integrated MSME empowerment model combining product innovation (milkfish dimsum diversification), branding, and digital marketing to strengthen household and village economic capacity. Method: A descriptive qualitative approach with a participatory action research design was applied, involving 28 members of PKK Mawar Mekar. Data were collected through participatory observation, semi-structured interviews, documentation, and structured training, then analyzed descriptively with source triangulation. Results: Findings indicate improvement in participants' cognitive, affective, and psychomotor competencies, marked by their capability to produce three hygienic milkfish dimsum variants, apply graphic-design-based branding and labeling, and independently manage digital promotional content. Analysis through Community Empowerment Theory, Human Capital Theory, Diffusion of Innovation, and Resource-Based View confirms that simultaneous integration of the three pillars accelerated participants' transformation from commodity driver to value driver. Implication: This study contributes a replicable empowerment model for coastal fisheries-based MSMEs and enriches community-empowerment literature on local commodity downstreaming.